Micro-structured fibre for sensing applications - Zhang, Qingxin (Nanyang Technological University, 2019)
Optical sensing is popular nowadays, specially in chemical and biological field. Measurement depends on the interaction between a target species and light, where the properties of the excitation light changes due to the property of the species or measured by generating another light signal which can be measure. Optical fibers are great material which can utilize this mechanism to create a sensor. Optical fibers have a well-defined optical guiding property, an ability to guide light to areas of interest, Optical fibers are compatible with Various kind of light sources such as LED, lasers and lamps, and detection devices. In this article, I will define the traditional optical fiber which used for optical communication as conventional optical fiber. Its core and cladding are made by concentric solid glass materials. The inner transmitting cylinder or the light ray has a diameter as small as 10μm and the total diameter of the fiber cable is about 0.125mm which is like a human hair [6]. Extrinsic sensing is where sensing is performed at the distal end of the fiber. However, there is a significant disadvantage of the conventional optical fiber where the interaction area is limited at the tip of the fiber. Many optical fiber sensor designers have been proposed and demonstrated to achieve intrinsic sensing. where the optical fiber is not simply a light carrier but make the light property change with in a portion of the optical field that propagates along the fiber. It is normally using in chemical and biological sensing. For example, D-shaped fibers which has a fragile structure. This is because the fiber cladding was removed. or tapering optical fiber which reduce the sensitivity due to the tapering affects the critical angle. It will allow the light interaction along the fiber length. Microstructured optical fibers (MOFs) has the advantage of the conventional optical fiber as well as its structure allows the interaction between the light and chemical species can be extended along the entire length of the fiber, while maintaining the integrity of the device. In suspended-core MOFs (SCMOFs), the glass core is suspended in air by thin struts, allowing a portion of the guided light to extend outside the fiber core into the surrounding holes which serve as low-volume sample chambers.[*] For exposed-core MOFs (ECMOFs), the suspended core is partly open to the environment, enabling easy access to the fiber core and removing the need for sample filling.[*] Hollow-core MOFs (HCMOFs) have also been used for sensing, where the air core not only guides light but also serves as the sample chamber, allowing large overlap of the guided light with the sample.The overlap of the guided light means that properties such as the refractive index and the absorption characteristics of the medium can alter the properties of the guided light. These fibers are an attractive platform for liquid sensing as they can enable strong light–matter interactions, long interaction lengths, and the use of small sample volumes. [*]